2017
DOI: 10.15252/emmm.201707795
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor gamma (PPARγ) regulates lactase expression and activity in the gut

Abstract: Lactase (LCT) deficiency affects approximately 75% of the world's adult population and may lead to lactose malabsorption and intolerance. Currently, the regulation of LCT gene expression remains poorly known. Peroxisome proliferator activator receptorγ (PPARγ) is a key player in carbohydrate metabolism. While the intestine is essential for carbohydrate digestion and absorption, the role of PPARγ in enterocyte metabolic functions has been poorly investigated. This study aims at characterizing PPARγ target genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Furthermore, the functional response element activated by PPARγ was identified in the promoter of the human GLB1 gene. PPARγ was also shown to regulate β-Gal expression and activity in the gut (Fumery et al 2017). Our data show a similar relation; moreover, we suggest a bidirectional interaction between Pparγ and β-Gal.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, the functional response element activated by PPARγ was identified in the promoter of the human GLB1 gene. PPARγ was also shown to regulate β-Gal expression and activity in the gut (Fumery et al 2017). Our data show a similar relation; moreover, we suggest a bidirectional interaction between Pparγ and β-Gal.…”
Section: Discussionsupporting
confidence: 81%
“…### P < 0.001 vs. the rosiglitazone or pioglitazone treated cells and VGVAPG co-treated with rosiglitazone or pioglitazone after 48 h of using Glb1 siRNA, we observed a decrease in the expression of both the β-Gal and Pparγ protein. Similar use of Pparγ siRNA caused a decrease in the expression of both the β-Gal and Pparγ protein after 48 h. It was found that PPARγ agonists are able to induce GLB1 mRNA expression and activity in Caco-2 cells (Fumery et al 2017). Furthermore, the functional response element activated by PPARγ was identified in the promoter of the human GLB1 gene.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The sterol regulatory elementbinding proteins (SREBP) pathway, involved in responding to low concentrations of cholesterol and subsequent promotion of cholesterol biosynthesis [37,38], was over-represented along with significant up-regulation of cholesterol biosynthesis genes SREBF2, DHCR7, INSIG1, ERLIN2, SQLE, IDI1 and LDLR (Fig 3, Table 2 and S5 Table). Immune-metabolic regulatory genes, PPARG (encoding the proliferator-activated receptor gamma protein, a nuclear receptor involved in controlling beta-oxidation of fatty acids and regulation of glucose metabolism) [39,40] and CEBPB (a transcription factor important for regulating immune and inflammatory response genes) were also up-regulated. Importantly, this metabolism sub-network indicated connections between cholesterol biosynthesis genes (i.e.…”
Section: Changes In Metabolic Pathwaysmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptors (PPARs): The three major PPARs are PPARa, PPARb/d, and PPARg [nuclear receptor subfamily 1, group C, members 1, -2, and -3, respectively]. In humans, PPARa is present mainly in liver, heart, and kidney; PPARb/d is in all organs evaluated including intestine (Peters et al, 2019); and PPARg in adipose tissue, large intestine, macrophages, monocytes, and Caco-2 cells (Dubuquoy et al, 2006;Couvigny et al, 2015;Fumery et al, 2017). Intestinal microbiota play key roles in intestinal inflammation via the production of PPAR agonists and antagonists, suggesting that PPAR may be involved in the pathophysiology of intestinal inflammatory diseases such as irritable bowel syndrome (Belmonte et al, 2012).…”
Section: Enteric Nuclear Receptorsmentioning
confidence: 99%